Need Analysis of Sundanese Cultural Infusion: Peaceful Education in Early Childhood Education Based - Gifari, Muhamad Kosim (PEDAGOGIA, 2024)
Peace education in early childhood is essential for fostering values such as self-awareness and conflict resolution from an early age. This study analyzed the need for integrating Sundanese culture-based peace education into early childhood education. A quantitative descriptive method was employed, utilizing a survey distributed to teachers and school principals in Soreang, Bandung Regency, through convenience sampling. The respondents, primarily teachers, completed a questionnaire via Google Forms. The findings indicated that most respondents viewed Sundanese cultural elements—such as the values of silih asah, silih asih, and silih asuh, along with traditional games—as effective mediums for teaching peace values to young children. However, respondents identified the need for additional resources, specialized training, and the integration of Sundanese cultural components into the curriculum to enhance implementation. In conclusion, the study underscores the urgency of incorporating Sundanese culture-based peace education into early childhood curricula. Ensuring its success requires adequate training, sufficient resources, and curriculum integration to equip educators with the tools and knowledge necessary for effective implementation.